The cyclic stability of superelasticity in aged Ti49.3Ni50.7 single crystals with oxide surface - Eftifeeva, Anna S.; Panchenko, Elena Yu; Fatkullin, Ilya D.; Volochaev, Mikhail N.; Tagiltsev, Anton I.; Chumlyakov, Yuri I. (Metals)
The cyclic stability of superelasticity in compression in [001]B2-oriented Ti49.3Ni50.7 single crystals is considered in this paper. The crystals were aged at 823 K for 1.0 h in air and helium. It has been experimentally shown that a two-layered surface thin film, consisting of a Ni-free oxide layer and a Ni-rich sublayer, appears after the oxidation at 823 K in air. The surface layers have a weak effect on the forward B2-R-B19’ martensitic transformation temperatures: TR temperature increases by 4 K;Ms and Mf temperatures decrease by 6 K. The oxide layer does not affect either the superelasticity response during fatigue tests or the temperatures of reverse B19’-B2 martensitic transformation. The cracking of the surface oxide layer during fatigue tests was not found in [001]B2-oriented single crystals aged in air. This is contributed by the relaxation of internal stresses. Such internal stresses are caused by both the formation of an oxide layer during aging and the matrix deformation at the stress-induced martensitic transformation. The main relaxation mechanisms of the internal stresses are the oriented growth of Ti3Ni4 precipitation near a thin surface film at aging in air, the formation of dislocations near the precipitation-matrix interface and a fine twinned B19’-martensite at fatigue tests.